PROJECT BASED LEARNING E-BOOK: TRAINING ECOPRENEURSHIP SKILLS FOR STUDENTS WITH TECHNOLOGICAL INNOVATION MATERIAL - Azizah, Siti Nur; Rahayu, Yuni Sri; Indah, Novita Kartika (JURNAL EDUSCIENCE, 2025)
Purpose – This study addressed the absence of interactive e-books to assist high school students in learning technological innovation, particularly biotechnology, while developing their ecopreneurship skills. In the era of 21st-century learning and the Merdeka Curriculum, students are expected to possess creative thinking, collaboration, and problem-solving skills. Therefore, this study aims to develop a Project-Based Learning (PjBL) e-book on technological innovation materials that are engaging, interactive, and capable of strengthening students' ecopreneurship competencies.Methodology – The research employed the 4D development model (Define, Design, Develop, Disseminate). Though limited to the development and validation stages, a purposive sampling technique involved three expert validators specializing in content, pedagogy, and biology. The assessment instrument covered content accuracy, visual presentation, and language quality. The data were analyzed using descriptive quantitative methods and validity percentages.Findings – The validation results indicated that the developed e-book is highly valid for use in learning, with a score of 99.25% for presentation, 97.8% for content, and 87.37% for language. The e-book is also equipped with multimedia features such as videos, images, and active links, which enhance interactivity and accessibility, making the learning process more engaging and meaningful.Contribution – This study contributes to educational technology by introducing a project-based digital learning medium that contextually fosters students' ecopreneurship skills. The developed e-book serves as a practical model for digital learning media that integrates scientific knowledge, environmental awareness, and entrepreneurial values.